Selfish personalities influencing start-up intention and motivation: A study of Vietnam - Tran Thi Hong Lien; Tran Tu Anh; Truong Nhat Anh; Le Huu Tuan Anh; Ngo Thi Thien Thao (Journal of Innovation and Entrepreneurship, 2022)
This research explores the influences of selfish personalities of the Dark Triad on start-up intention and motives based on a sample of 400 university students in Vietnam, discovering mixed effects of narcissism, psychopathy, and Machiavellianism. A high level of narcissism and Machiavellianism leads to high start-up intention. There is a negative relationship of Machiavellianism with pro-social motive and a positive association with selfish entrepreneurship. In addition, narcissism is positively associated with pro-social start-up motives. This study has found no effect of psychopathy but a positive link to selfish entrepreneurial motivation. Implications have been suggested for educators and investors.
Keywords: 650; Dark triad; Entrepreneurship; Selfish personality; Start-up; Vietnam